2015 Annual IEEE Systems Conference (SysCon) Proceedings 2015
DOI: 10.1109/syscon.2015.7116810
|View full text |Cite
|
Sign up to set email alerts
|

OPM & color petri nets based executable system of systems architecting: A building block in FILA-SoS

Abstract: The ability to coordinate intricate operations in both intelligence, surveillance and reconnaissance (ISR) as well as search and rescue (SAR) operations is a complex issue. Such operations can be described as a System-of-Systems (SoS). Both object process methodology (OPM) and color petri nets (CPN)can be used to create executable architecture models for an SoS.The modeling approach proposed in this study can capture the interactions that occur between either collaborating systems or components. It can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…(s1) [Teixeira et al 2020], (s2) [Binder et al 2019], (s3) [Manzano et al 2019], (s4) [Beery et al 2019], (s5) [Graciano Neto et al 2018b], (s6) [Zhang et al 2018], (s7) [Graciano Neto et al 2018a], (s8) [Zhuang et al 2018], (s9) [Esmaeilzadeh et al 2018], (s10) [Dahmann et al 2017], (s11) [Graciano Neto et al 2017], (s12) [Silva et al 2017], (s13) [Hachem et al 2016], (s14) [Oquendo et al 2016], (s15) [Li et al 2013], (s16) [Yousefi and Levis 2016], (s17) [Arnold et al 2016], (s18) [Spichkova et al 2015], (s19) [Li et al 2016b], (s20) [Wang et al 2015], (s21) [Cavalcante 2015], (s22) [Wätzoldt and Giese 2015], (s23) [Perišić et al 2015], (s24) [Hu et al 2014], (s25) [Hsu et al 2014], (s26) [Rieckmann et al 2013], (s27) [Ge et al 2013], (s28) [Li et al 2013], (s29) [Ludwig et al 2011], (s30) [Wang and Dagli 2011], (s31) [Xiong et al 2010], (s32) [Garcia and Tolk 2010], (s33) [Sindiy et al 2009], (s34) [Robbins 2009], (s35) [Rao et al 2008]. We answer the raised research questions, as follows.…”
Section: Reportingmentioning
confidence: 99%
See 4 more Smart Citations
“…(s1) [Teixeira et al 2020], (s2) [Binder et al 2019], (s3) [Manzano et al 2019], (s4) [Beery et al 2019], (s5) [Graciano Neto et al 2018b], (s6) [Zhang et al 2018], (s7) [Graciano Neto et al 2018a], (s8) [Zhuang et al 2018], (s9) [Esmaeilzadeh et al 2018], (s10) [Dahmann et al 2017], (s11) [Graciano Neto et al 2017], (s12) [Silva et al 2017], (s13) [Hachem et al 2016], (s14) [Oquendo et al 2016], (s15) [Li et al 2013], (s16) [Yousefi and Levis 2016], (s17) [Arnold et al 2016], (s18) [Spichkova et al 2015], (s19) [Li et al 2016b], (s20) [Wang et al 2015], (s21) [Cavalcante 2015], (s22) [Wätzoldt and Giese 2015], (s23) [Perišić et al 2015], (s24) [Hu et al 2014], (s25) [Hsu et al 2014], (s26) [Rieckmann et al 2013], (s27) [Ge et al 2013], (s28) [Li et al 2013], (s29) [Ludwig et al 2011], (s30) [Wang and Dagli 2011], (s31) [Xiong et al 2010], (s32) [Garcia and Tolk 2010], (s33) [Sindiy et al 2009], (s34) [Robbins 2009], (s35) [Rao et al 2008]. We answer the raised research questions, as follows.…”
Section: Reportingmentioning
confidence: 99%
“…RQ1 -What research treads can be observed over the years? Interestingly, even after the rise of automatic transformation approaches, it is still possible to identify studies that manually synthesize the architecture proposal into ExM [Beery et al 2019, Esmaeilzadeh et al 2018, Hsu et al 2014, Teixeira et al 2020, Wang et al 2015, Yousefi and Levis 2016. No convergence in the community towards a common technology or tool was observed.…”
Section: Reportingmentioning
confidence: 99%
See 3 more Smart Citations